(untitled) (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Bianca-Maria Partenie explores laughter as a mechanism for deconstructing narrative forms in the avant-garde works of Urmuz and Daniil Harms. By subverting literary conventions, these authors use humor to sabotage traditional elements like characters and narrators. Laughter acts as a tool that dismantles old patterns while building a new, subjective logic. Through absurdity and parody, they transform classic storytelling into "false narratives," inviting readers to experience a subversive, bizarre, and creatively liberating reality. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.